HIV-1 resists MxB inhibition of viral Rev protein - Zhen Wang; Keli Chai; Qian Liu; Dong-Rong Yi; Qinghua Pan; Yu Huang; Juan Tan; Wentao Qiao; Fei Guo; Shan Cen; Chen Liang (Emerging Microbes and Infections, 2020)
ABSTRACTThe interferon-inducible myxovirus resistance B (MxB) protein has been reported to inhibit HIV-1 and herpesviruses by blocking the nuclear import of viral DNA. Here, we report a new antiviral mechanism in which MxB restricts the nuclear import of HIV-1 regulatory protein Rev, and as a result, diminishes Rev-dependent expression of HIV-1 Gag protein. Specifically, MxB disrupts the interaction of Rev with the nuclear transport receptor, transportin 1 (TNPO1). Supporting this, the TNPO1-independent Rev variants become less restricted by MxB. In addition, HIV-1 can overcome this inhibition by MxB through increasing the expression of multiply spliced viral RNA and hence Rev protein. Therefore, MxB exerts its anti-HIV-1 function through interfering with the nuclear import of both viral DNA and viral Rev protein.